Examining the Role of School Leadership Styles in Promoting School’s Performance and Academic Success in UAE: A Systematic Review-Based Analysis - Atteya, Rasha Ahmed Fouad Abdelhady Ahmed (2025)
Academic success in schools today depends on the effectiveness of the leadership styles of school leaders. Amidst the accelerated change such as e-learning and evolving student demands, successful leadership affects the performance of both teachers and students. This study examines the influence of different leadership styles on the performance of schools through a systematic literature review, focusing on research from 2013 to 2024. The methodology involves a critical review of relevant literature on the effects of different forms of leadership approaches in schools. The analysis synthesizes evidence, establish trends among different learning settings, and assess determinants of effective leadership. The paper contributes to the debate on guidelines for assisting school leaders understand and apply the most effective leadership styles in varying situations. It proposes leadership approaches that optimize teacher satisfaction, student achievement, and school success. These include models such as transformational and democratic leadership, which induce motivation, shared decision making, along with innovation. This study contributes to the discourse on how school administrators can map current plans to institutional objectives and community aspirations within UAE.